Enlargement of the Internal Auditory Canal and Associated Posterior Fossa Anomalies in PHACES Association - Meltzer, D.E. (AJNR Am J Neuroradiol, 2015)
We noted enlargement of the internal auditory canal in several of our patients with posterior fossa malformations, hemangiomas, arterial anomalies, cardiac defects, eye abnormalities, and sternal or supraumbilical defects (PHACES) association and hence evaluated children with PHACES for the presence of an enlarged internal auditory canal and potential associated findings, including infantile hemangioma within the internal auditory canal, to understand the genesis of this enlargement. We reviewed our records to identify children with PHACES association who had been evaluated with MR imaging at our institutions. Imaging was reviewed for abnormal enhancement in the internal auditory canal, internal auditory canal enlargement, cerebellar hypoplasia, prominence of the petrous ridge, and deformity of the calvarium. We raise the possibility of an association between enlargement of the internal auditory canal in PHACES and a generalized malformation of the posterior fossa with cerebellar and calvarial hypoplasia.